2000
DOI: 10.1073/pnas.050586197
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CDK4 as a target of c-MYC

Abstract: The prototypic oncogene c-MYC encodes a transcription factor that can drive proliferation by promoting cell-cycle reentry. However, the mechanisms through which c-MYC achieves these effects have been unclear. Using serial analysis of gene expression, we have identified the cyclin-dependent kinase 4 (CDK4) gene as a transcriptional target of c-MYC. c-MYC induced a rapid increase in CDK4 mRNA levels through four highly conserved c-MYC binding sites within the CDK4 promoter. Cell-cycle progression is delayed in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
337
1

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 430 publications
(352 citation statements)
references
References 35 publications
14
337
1
Order By: Relevance
“…Expression of WS5 is tightly correlated with Myc levels, the promoter region contains a cluster of Myc-binding sites that are occupied in vivo by Myc and Max, and transactivation analyses of the wild-type and mutant versions of the promoter directly proved functionality of these sites. Clustering of multiple E-boxes increases the chances of recruiting multiple Myc-Max complexes to a gene, leading to synergistic activation (Hermeking et al, 2000;Levens, 2003). This is directly supported by our data (see Figure 4).…”
Section: Ws5 a Direct Transcriptional Target Of Myc F Reiter Et Alsupporting
confidence: 87%
See 1 more Smart Citation
“…Expression of WS5 is tightly correlated with Myc levels, the promoter region contains a cluster of Myc-binding sites that are occupied in vivo by Myc and Max, and transactivation analyses of the wild-type and mutant versions of the promoter directly proved functionality of these sites. Clustering of multiple E-boxes increases the chances of recruiting multiple Myc-Max complexes to a gene, leading to synergistic activation (Hermeking et al, 2000;Levens, 2003). This is directly supported by our data (see Figure 4).…”
Section: Ws5 a Direct Transcriptional Target Of Myc F Reiter Et Alsupporting
confidence: 87%
“…For validation of a direct target, binding of Myc in vivo and tight correlation of transcriptional alterations with Myc expression is required (Eisenman, 2001). Several direct Myc targets have been well defined (Dang, 1999;Grandori et al, 2000;Hermeking et al, 2000;Eisenman, 2001;Patel et al, 2004), most of them with biological functions in cell cycle control, metabolism or ribosome biogenesis, but only a few have so far been directly linked to the transforming function of Myc (Eisenman, 2001, Patel et al, 2004. These include the ornithine decarboxylase gene (ODC), the tumor-associated membrane glycoprotein gene Tmp, the metastasis-associated protein 1 (MTA1) gene, or the transferrin receptor 1 (TFRC1) gene, that were shown to have oncogenic potential (BenPorath et al, 1999;Eisenman, 2001;Zhang et al, 2005;O'Donnell et al, 2006).…”
Section: Ws5 a Direct Transcriptional Target Of Myc F Reiter Et Almentioning
confidence: 99%
“…To investigate potential links between Myc and p18 Ink4c , we initially used Affymetrix gene chip microarray analysis and compared the expression of Ink4c to that of other Ink4 family members, CKIs, Cdk4 and Cdk6 in B220 þ splenocytes isolated from wild-type and precancerous Em-Myc transgenic littermates ( Figure 1a). As expected, Cdk4 (a known Myc target (Hermeking et al, 2000)) was elevated in precancerous (4-to 6-week-old) splenic B cells from Em-Myc mice, whereas these cells expressed reduced levels of Cdkn1b (encoding p27 Kip1 ). By contrast, Ink4c (Cdkn2c) expression was induced in Em-Myc B cells (Po0.05), and there were no significant changes in the expression of Ink4a (Cdkn2a) or Ink4d (Cdkn2d).…”
Section: P18supporting
confidence: 75%
“…Myc overexpression accelerates cell cycle progression (Roussel et al, 1991), and this occurs through their induction of D-type cyclins (Bouchard et al, 1999) and their partner Cdk4 (Hermeking et al, 2000), as well as by repressing p21 Cip1 (Herold et al, 2002;Seoane et al, 2002;Wu et al, 2003), p27 Kip1 (Yang et al, 2001), p15 Ink4b Staller et al, 2001) and p18 Ink4c (Knoepfler et al, 2002). However, in normal cells this proliferative response is counterbalanced by Myc's ability to provoke apoptosis (Askew et al, 1991;Evan et al, 1992;Eischen et al, 1999;Pelengaris et al, 2002;Nilsson and Cleveland, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The observation that potent cell cycle regulators, such as SV40 Tantigen and adenovirus E1A, did not rescue the slow growth phenotype of the c-myc null cells suggests that the cell cycle components that are deregulated by these viral proteins are not among the critical targets of cMyc. Recently, the cyclin-dependent kinase CDK4 was identi®ed as a critical target of c-Myc since it could partially alleviate the c-myc null growth defect (Hermeking et al, 2000). However, in our hands a cmyc null derivative that over-expressed the tumorderived CDK4/R24C mutant (Wolfel et al, 1995) did not even show a partial rescue of the growth defect (data not shown).…”
Section: Abstract: C-myc; Cell Proliferation; Cell Cyclementioning
confidence: 58%